The Influence of The Phrase 'Online' on the Fulfillment of Public Participation in the Formation of Laws Through the DPR Legislative Information System - Pujianti, Yuwinda Sari; Perwira, Indra; Junaenah , Inna (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This research aims to analyze the influence of the phrase 'Online' on the fulfillment of Public Participation in Law Formation through the DPR's legislative information system. This research uses a normative legal research approach which includes legislative, conceptual and historical approaches. Method: The data collection approach in this research is library research. The data obtained is then processed through three stages, namely data reduction, data presentation, and drawing conclusions. Results: Research findings show that the term 'online' in article 96 of Law Number 13 of 2022 requires the DPR to be able to assist in implementing community involvement, one of which is through sileg. Apart from that, based on the provisions of Secretary General Number 13 of 2020 and the parliamentary website guidelines that have been prepared by the IPU, improvements and developments need to be made in the implementation of Sileg. Novelty: The novelty of this research comes from the research object, namely the formation of laws through the DPR Legislative Information System in the context of the influence of the phrase 'Online' on the fulfillment of community participation. Conclusion: Adequate information in Sileg at all stages of law formation can facilitate and encourage public participation in providing input on each bill that is being discussed and/or will be discussed in the DPR. The ideal implementation of sileg is as an online medium for people to carry out more meaningful community activities.